Traditional Cardiovascular Risk Factors and Coronary Collateral Circulation: A Meta-Analysis - Pei, Junyu; Wang, Xiaopu; Xing, Zhenhua (Frontiers in Cardiovascular Medicine, 2021)
Objective: Patients with well-developed coronary collateral circulation (CC) usually have low mortality, improved cardiac function, and reduced infarct size. Currently, there is conflicting evidence on the association between traditional cardiovascular risk factors (diabetes, hypertension, and smoking habit) and CC. Design: We performed a meta-analysis of case-control studies to better understand such associations. Data sources: We searched the MEDINE, EMBASE, and Science Citation Index databases to identify relevant studies. Eligibility criteria for selecting studies: Case control studies reporting data on risk factors (smoking habit, hypertension, and diabetes mellites) in comparing cases between poor CC and well-developed CC groups. Well-developed CC was the primary outcome of this meta-analysis Data extraction and synthesis: Relevant data were extracted by two independent investigators. We derived pooled odds ratios (ORs) with random effects models. We performed quality assessments, publication bias, and sensitivity analysis to ensure the reliability of our results. Results: In total, 18 studies that had 4,746 enrolled patients were analysed. Our results showed that hypertension and smoking habit did not (OR = 0.94, 95% CI: 0.75–1.17, p = 0.564 and OR = 1.00, 95% CI: 0.84–1.18, p = 0.970, respectively), and diabetes did (OR = 0.50, 95% CI: 0.38–0.67, p = 0.00001) affect the development of CC. Conclusion: Unlike hypertension and smoking habit, diabetes was associated with poor CC formation.